2022
DOI: 10.1002/jev2.12234
|View full text |Cite
|
Sign up to set email alerts
|

αvβ1 integrin is enriched in extracellular vesicles of metastatic breast cancer cells: A mechanism mediated by galectin‐3

Abstract: Breast cancer cells release a large quantity of biocargo-bearing extracellular vesicles (EVs), which mediate intercellular communication within the tumour microenvironment and promote metastasis. To identify EV-bound proteins related to metastasis, we used mass spectrometry to profile EVs from highly and poorly metastatic breast cancer lines of human and mouse origins. Comparative mass spectrometry indicated that integrins, including αv and β1 subunits, are preferentially enriched in EVs of highly metastatic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…More specifically, in the context of cancer (and retinoblastoma), EVs play an important role in tumor progression as messengers in cellular interactions and homeostasis of the tumor microenvironment. For instance, studies have shown that cancer EVs with specific surface markers, such as integrins [ 64 , 65 ] or proteoglycans [ 66 , 67 ], can enhance the endocytic uptake of EVs within tumor cells. Hence, the unique characteristics of cancer EVs make them a promising drug delivery system because they could be loaded with chemotherapeutics (with increased endocytic delivery to tumors) and used as a novel cancer treatment; this remains unexplored to date in retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, in the context of cancer (and retinoblastoma), EVs play an important role in tumor progression as messengers in cellular interactions and homeostasis of the tumor microenvironment. For instance, studies have shown that cancer EVs with specific surface markers, such as integrins [ 64 , 65 ] or proteoglycans [ 66 , 67 ], can enhance the endocytic uptake of EVs within tumor cells. Hence, the unique characteristics of cancer EVs make them a promising drug delivery system because they could be loaded with chemotherapeutics (with increased endocytic delivery to tumors) and used as a novel cancer treatment; this remains unexplored to date in retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…In Y79 cells, we found that a substantially higher proportion of breast cancer EVs were endocytosed than non-cancerous ocular epithelial EVs. We propose that the accumulation of breast cancer EVs is related to the molecular composition of surface markers [ 64 , 65 ], which increases their capacity to become endocytosed compared to non-cancerous EVs. EV membrane proteins could include tetraspanins, integrins, or heparin sulfate proteoglycans; these may trigger increased cellular uptake by Y79 cells and mediate changes in signaling cascades [ 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…3) (88). This study highlights the potential of sEVs-bound integrin avb1 as a novel prognostic and therapeutic target in BC metastasis.…”
Section: Involvement Of Sevs In Bc Invasion and Metastasismentioning
confidence: 75%
“…They demonstrated that integrin αv was detected more frequently in circulating sEVs of patients with late-stage (III and IV) than early-stage (I and II) BC. Further analysis revealed integrin αvβ1 is linked to sEVs from metastatic BC cells, whose export into sEVs is in part regulated byβ-Galactose lectin-3(Gal-3) ( 88 ). This study highlights the potential of sEVs-bound integrin αvβ1 as a novel prognostic and therapeutic target in BC metastasis.…”
Section: Sevs Derived From Breast Cancer and Their Role In Cancer Pro...mentioning
confidence: 99%
“…Galectin-3 might regulate the loading integrin αv and β1 in EVs. [ 176 ] ITGB4 Breast cancer Induces BCL2 interacting protein 3 like (BNIP3L)-dependent mitophagy and glycolysis. [ 33 ] Sphingosine 1 Breast cancer Sphingosine 1 drived from cancer cells may stimulate ERK-1/2 signalling and DNA synthesis [ 73 ] Survivin Breast cancer Generate CAFs with myofibroblastic features through inducing SOD1 expression to promote tumour proliferation and metastasis [ 74 ] Wnt2B Cervical cancer Generate CAFs through activating Wnt/β-catenin signalling [ 75 ] HSPC111 Colorectal cancer Reprogramming lipid metabolism in CAFs to promote cancer metastasis.…”
Section: Cancer-derived Evs Can Dictate Preferable Caf Characteristic...mentioning
confidence: 99%